Community health workers' perceptions of the government's guideline on the use of fats and oils in the daily diet of Filipinos - Tablante, Josephine F. (2006)
National nutrition surveys had consistently shown that Filipinos do not meet their daily energy requirement; this has been attributed to their low intake of dietary fat. In view of this, the Nutritional Guidelines for Filipinos 2000 recommends "eat foods cooked in edible/cooking oil daily" or in Filipino "kumain araw-araw ng mga pagkaing niluto sa langis/edible oil."This specific guideline and others are explained in a handbook recommended for use of field workers for their nutrition education activities. This study determined the community health workers' perceptions of the national government's guideline on the use of fats and oils, as a whole and in terms of its key concepts. Four focus group discussions were conducted using the Filipino language. Twenty-nine females, 32 to 59 years of age and with elementary school education participated in the study. The community health workers perceived the guidelines not only from a technical or scientific standpoint. They were not in favor of the government's recommendation because of specific considerations related to health, cost of oil, food preferences and day-to-day food-related practices. Moreover, since there are many ways of increasing fat intake, zeroing in on cooking foods in oil was considered a limited approach. The respondents perceived "edible oil" as food, whereas "langis" is in the local language, it was perceived as meant for lower income groups whereas "edible oil" is for higher income groups because it is written in English. On the whole, the health workers' conceptualization of the guideline is more broadly based compared to those who developed it since the respondents did not limit themselves to technical or scientific considerations. The two groups also differed in terms of health rationale for the guideline and the appropriateness and usefulness of the recommendation. Moreover, contrary to the claim that the guideline is clear and understandable to elementary graduates and need no further explanation, the health workers, all of whom completed the elementary grades, had difficulties comprehending the guideline. To analyze the results of the study, the guideline was compared to other nutrition education materials on the subject of fats and oils. The guideline does not appear to be consistent with existing Food Guide Pyramid made by the government and private sector. To enhance understanding of the guideline by the health workers, and through them, the general public, it is recommended that the guideline be re-evaluated, through appropriate research studies, taking into account existing perceptions, knowledge and practices of target audience and consistency among nutrition education materials.